2020
DOI: 10.1038/s41408-020-00372-5
|View full text |Cite
|
Sign up to set email alerts
|

Multiple myeloma and SARS-CoV-2 infection: clinical characteristics and prognostic factors of inpatient mortality

Abstract: There is limited information on the characteristics, prognostic factors, and outcomes of patients with multiple myeloma (MM) hospitalized with COVID-19. This retrospective case series investigated 167 patients reported from 73 hospitals within the Spanish Myeloma Collaborative Group network in March and April, 2020. Outcomes were compared with 167 randomly selected, contemporary, age-/sex-matched noncancer patients with COVID-19 admitted at six participating hospitals. Among MM and noncancer patients, median a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 27 publications
(24 reference statements)
2
66
0
1
Order By: Relevance
“…The ongoing COVID-19 pandemic has even shed a light on the importance of comorbidities, where up to 75% MM patients who got infected by the virus and admitted to hospital had a comorbidity at diagnosis, and over 80% of patients who died from COVID suffered from other diseases than MM. 35 In the current study, 14 diseases were related to a higher risk of death. Patients with dementia had the highest risk of death (72% higher), followed by heart failure which increased the risk by 54%.…”
Section: Discussionmentioning
confidence: 49%
“…The ongoing COVID-19 pandemic has even shed a light on the importance of comorbidities, where up to 75% MM patients who got infected by the virus and admitted to hospital had a comorbidity at diagnosis, and over 80% of patients who died from COVID suffered from other diseases than MM. 35 In the current study, 14 diseases were related to a higher risk of death. Patients with dementia had the highest risk of death (72% higher), followed by heart failure which increased the risk by 54%.…”
Section: Discussionmentioning
confidence: 49%
“…A recent study from Spain found a higher mortality rate in MM patients with COVID-19 (34%) compared with age- and sex-matched non-MM patients with COVID-19 (23%). 21 A recent publication from France confirmed overall mortality in all hospitalized patients with COVID-19 to be 16%, which is significantly lower than mortality observed in hospitalized MM patients in France (39%). 22 Our data clearly suggest a lack of relationship between prior lines of therapy or prior type of therapy, or those receiving active MM therapy at the time of diagnosis with COVID-19 and outcome.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, they were demonstrated that uncontrolled MM and renal insufficiency were independent factor of death in hospitalized patients with COVID19. 9 Besides, this case presented poor prognostic factor: age >65 years, progressive disease, and renal disease.…”
Section: Discussionmentioning
confidence: 80%